Mutation of the Sry-related Sox10 gene in Dominant megacolon, a mouse model for human Hirschsprung disease - Herbarth, Beate (The National Academy of Sciences, 1998)
The spontaneous mouse mutant Dominant megacolon (Dom) is a valuable model for the study of human congenital megacolon (Hirschsprung disease). Here we report that the defect in the Dom mouse is caused by mutation of the gene encoding the Sry-related transcription factor Sox10. This assignment is based on (i) colocalization of the Sox10 gene with the Dom mutation on chromosome 15; (ii) altered Sox10 expression in the gut and in neural-crest derived structures of cranial ganglia of Dom mice; (iii) presence of a frameshift in the Sox10 coding region, and (iv) functional inactivation of the resulting truncated protein. These results identify the transcriptional regulator Sox10 as an essential factor in mouse neural crest development and as a further candidate gene for human Hirschsprung disease, especially in cases where it is associated with features of Waardenburg syndrome.